2023
DOI: 10.1136/bmjopen-2022-068126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self-disclosure and resilience on reproductive concern in patients of childbearing age with breast cancer: a cross-sectional survey study

Abstract: ObjectivesTo assess reproductive concerns in patients of childbearing age with breast cancer and examine the relationship between self-disclosure, resilience and reproductive concerns.DesignCross-sectional survey.SettingFive tertiary first-class general hospitals in Sichuan Province, Southwest China.ParticipantsA total of 319 patients with breast cancer of reproductive age who were hospitalised in the breast oncology department participated in this study.Main outcome measuresPrimary outcomes were the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…The median self--disclosure score of the older adult homebound breast cancer patients in this study was 37 (moderate level), lower than that of Zhu et al (2023) (40.41 ± 7.34) for resident breast cancer patients. There are several reasons for the low self-disclosure scores of older adult homebound breast cancer patients.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The median self--disclosure score of the older adult homebound breast cancer patients in this study was 37 (moderate level), lower than that of Zhu et al (2023) (40.41 ± 7.34) for resident breast cancer patients. There are several reasons for the low self-disclosure scores of older adult homebound breast cancer patients.…”
Section: Discussioncontrasting
confidence: 65%
“…There are several reasons for the low self-disclosure scores of older adult homebound breast cancer patients. First, for age-related reasons, Zhu et al (2023) found that the study population was 25–49 years old, which belonged to the middle-aged and young stage, whereas the study population was older adults aged over 60 years. The difference in age between the two groups may also be an important factor influencing the lower self-disclosure level of older adults with breast cancer in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Introverts tend to have higher AG scores, most introverts are not very expressive and with their own illnesses they may prefer to choose to keep themselves to themselves. In contrast, extroverts are willing to talk to others and like to express their thoughts, and in the exposure emotional cognition might change thereby lowering AG (Zhu et al, 2023). Symptoms affect the patient's view of the disease, causing biased perceptions (Guan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%